The speed of serial attention shifts in visual search: Evidence from the N2pc component - Grubert, A.; Eimer, M. (Journal of Cognitive Neuroscience, 2016)
Finding target objects among distractors in visual search display is often assumed to be based on sequential movements of attention between different objects. However, the speed of such serial attention shifts is still under dispute. We employed a search task that encouraged the successive allocation of attention to two target objects in the same search display and measured N2pc components to determine how fast attention moved between these objects. Each display contained one digit in a known color (fixed-color target) and another digit whose color changed unpredictably across trials (variable-color target) together with two gray distractor digits. Participants' task was to find the fixed-color digit and compare its numerical value with that of the variable-color digit. N2pc components to fixed-color targets preceded N2pc components to variable-color digits, demonstrating that these two targets were indeed selected in a fixed serial order. The N2pc to variable-color digits emerged approximately 60 msec after the N2pc to fixed-color digits, which shows that attention can be reallocated very rapidly between different target objects in the visual field. When search display durations were increased, thereby relaxing the temporal demands on serial selection, the two N2pc components to fixed-color and variable-color targets were elicited within 90 msec of each other. Results demonstrate that sequential shifts of attention between different target locations can operate very rapidly at speeds that are in line with the assumptions of serial selection models of visual search.
EPrint Processing Status: Full text deposited in DRO